Sow patterned feeding method and its feed in gestation period - LIU YAN; XU JIE; SUN YANAN; YUE LONGYAO; WU KUN; SHAO CAIMEI; HU GUOQING; FENG WEIJIE (2018)
The invention belongs to the technical field of cultivation, and particularly relates to a sow patterned feeding method, and smashed feed for pregnant sow with low protein and high fiber in early andmedium periods of gestation. The sow feed in pregnant period is fed for 0-90 days after hybridization, and the specific feed amount is determined upon P2 backfat and body condition score. The sow feedin pregnant period is based on corn, bean pulp, extruded soybean, fine wheat bran, rice bran and others, and especially added with alfalfa grain, expanded flaxseed, fermented astragalus membranaceus,and Spanish bayonet plant extractive. The ratio of digestible amino acid is proper. By adopting the patterned feeding method, combining with sow feed in pregnant period, and applying a scientific feeding method, the sow weight and body condition are moderately controlled, the health birth number can be correspondingly increased, the sow birth performance is improved, and the sow mortality is reduced, and the sow feeding be